NAVIGATING THE SHIFT: HOW CASHLESS PAYMENTS, INTEREST RATES, AND COVID-19 AFFECT MONEY SUPPLY - Nofita, Fifi; Wahyuningsih, Diah (Universitas Tidar, 2024)
The purpose of this study was to find out how the influence of non-cash payments (debit cards, credit cards, and e-money), BI7DRR interest rates, and the impact of covid-19 on the money supply in Indonesia. The data used is monthly time series data, from September 2018 to August 2021. This study uses a quantitative approach using the Error Correction Model (ECM) method. The data analysis techniques used include: stationarity test, cointegration test, long-term and short-term ECM estimation, classical assumption test, and hypothesis testing. The results show that in the long-term debit cards and e-money have a positive and significant effect on money supply, credit cards and dummy (the impact of covid-19) have no significant effect on money supply, interest rates have a negative and significant effect on money supply. While in the short-term debit cards and dummy (the impact of covid-19) have a positive and significant effect on money supply, credit cards, e-money, and interest rates have no significant effect on money supply.